Therapeutic potential of neural stem cells preconditioned with baicalein-enriched fraction in Ischemic stroke rat model - Nik Salleh @ Nik Abdullah, Nik Nur Hakimah (2023)
Ischemic stroke, triggered by the abrupt interruption of cerebrovascular blood flow, could lead to permanent neuronal cell death. Recently, multipotent neural stem cell (NSC) grafting has emerged as potential therapy to regenerate the damaged brain tissue. However, the hostile microenvironment in the ischemic brain region is challenging for the survival of transplanted cells. In this regards, NSC culture was optimized with baicalein-enriched fraction (BEF) from Oroxylum indicum- to enhance the NSC survival rate after transplantation into ischemic brain. Baicalein is one of the major flavonoids present in O. indicum and has been reported to have neuroprotective effects. In this study, BEF was successfully fractionated from the leaves of O. indicum and quantified using HPLC and its radical scavenging activity was compared to synthetic baicalein as positive control. Ischemic stroke rat model was established using endothelin-1 (ET-1) which constrict the middle cerebral artery (MCA) to induce ischemic damage in the brain. In vitro expandable NSCs were preconditioned with BEF at optimum dosage of 3.125 μg/ml for 48 hours as determined through MTT assay before the cells were transplanted into the ET-1 induced ischemic stroke rat groups. Rat behaviours and stroke severity were observed and recorded for 14 days. Improvements in stroke behaviours occurred within 14 days after the transplantation of BEF-preconditioned NSC compared to non-preconditioned NSC transplantation group. Through TTC staining, the BEF-preconditioned NSC-treated group showed significant reduced brain infarct (11.535 ± 1.44%), compared to non-preconditioned NSC-treated group (17.784 ± 2.33%) and non-treated group (23.807 ± 2.60%). In addition, BEF-preconditioned NSC-treated group also significantly reduced neuronal degradation and inflammation, while also increased blood vessel density compared to the other groups. As a conclusion, this study proved the potential of BEF extracted from O. indicum in contributing to the upregulation of NSC proliferation- and significantly improved the therapeutic potential of NSCs to repair damaged neuronal tissue- ischemic stroke rats.